Different drought‑adaptive capacity of a native Patagonian tree species (Nothofagus pumilio) resulting from local adaptation - Soliani, Carolina; Mattera, María Gabriela; Marchelli, Paula; Azpilicueta, Maria Marta; Dalla Salda, Guillermina (Springer, 2022)
The resistance of different genotypes to abiotic stress may be due to genetic effects and/or to phenotypic plasticity allowing them to acclimate to variable conditions. The contribution of one or the other mechanism determines different strategies with implications for the species conservation and adaptive management. In this study, the ecophysiological response to drought of Nothofagus pumilio provenance sites (humid, mesic and xeric) from contrasting precipitation regimes was evaluated in a common garden trial. Seedlings were submitted to progressive drought by withdrawing irrigation (control vs water deficit). Assuming a genetic base determined by selection pressures, populations from more xeric sites are expected to show higher resistance to drought, e. g., higher resistance to xylem cavitation and safety margin, stronger stomatal control and osmotic adjustment. Vulnerability to cavitation curves were performed, and the percentage loss of conductivity (P12, P50, P88 and slope) was obtained. The water potential at turgor loss point (TLP) and the osmotic potential at full turgor (π100) were calculated from pressure–volume curves. The humid site showed a significantly higher P50 value than the mesic and the xeric sites. Pre-dawn water potential differed between the provenances from xeric and mesic conditions under severe water deficit. Natural selection was inferred from the comparison of differentiation at neutral markers and phenotypic traits (FST vs. PST), with signals of adaptive variation (PST > FST) for stomatal density, specific leaf area, TLP, π100 and stomatal conductance. Results suggest a differential adaptive capacity to drought of N. pumilio provenance sites that could be evidencing local adaptation to their home environment.